Figure Volume Calculation Based on Lidar Scanning Technology. Issue 1 (1st March 2023) - Wang, Feng; Zhang, Xiaojie; Wang, Wei; Zhang, Kaikai
Abstract: Aiming at the problems of earthmoving, low efficiency and complex calculation of ground object volume in the process of traditional engineering operation, a volume calculation method based on lidar scanning technology is proposed in this paper. The point cloud data of space volume was obtained by UAV lidar scanning system, and the regular grid method was used to resample the point cloud and obtained the volume of space volume. Taking the vehicle as an example, collected the twice point cloud data of the ground and the vehicle, calculated the trajectory and coordinates, the original data are pre-processing and resampled. The volume of surface vehicle was calculated by dividing regular grid and compared with the actual volume. The error was only 0.19% at the resampling interval of 0.25m. The results show that the method has high calculation efficiency and precision, and provides a reference for relevant engineering applications.